2017
DOI: 10.1016/j.maturitas.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hormone replacement therapy and tibolone on lipoprotein (a) concentrations in postmenopausal women: A systematic review and meta-analysis

Abstract: HRT significantly decreases Lp(a) concentrations, with oral being more effective than transdermal estradiol. The type of HRT, dose of estrogen and addition of progestogen do not seem to modify the Lp(a)-lowering effect of HRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 70 publications
2
44
0
6
Order By: Relevance
“…If there were any (unlikely) effect of fasting status on Lp(a) and Apo B and A1 levels, this should affect cases and referents equally and attenuate the results. Similarly, we do not have data on menopausal status or statin usage, which could affect levels of Lp(a) and Apo B and A1 10. However, because age is a matching criterion, a woman in menopause is most probably matched with female referents in menopause.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…If there were any (unlikely) effect of fasting status on Lp(a) and Apo B and A1 levels, this should affect cases and referents equally and attenuate the results. Similarly, we do not have data on menopausal status or statin usage, which could affect levels of Lp(a) and Apo B and A1 10. However, because age is a matching criterion, a woman in menopause is most probably matched with female referents in menopause.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, we do not have data on menopausal status or statin usage, which could affect levels of Lp(a) and Apo B and A1. 10 However, because age is a matching criterion, a woman in menopause is most probably matched with female referents in menopause. The usage of statins at the time of survey was probably very low, as the majority were surveyed before year 2000 (89%), and 98% did not report any MI before the survey.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, tibolone, a synthetic steroid with gestagenic and weak androgenic and estrogenic properties, resulted effective in reducing circulating Lp(a) levels (Haenggi, Riesen, & Birkhaeuser, ; Kotani et al, ). A recent meta‐analysis confirmed that hormone replacement therapy and tibolone reduced plasma Lp(a) concentrations in a large sample of postmenopausal women (Anagnostis et al, ). In line with these results, the selective estrogen receptor modulator raloxifene was reported to reduce plasma Lp(a) levels in a meta‐analysis of 1,378 post‐menopausal women (Ferretti et al, ).…”
Section: Therapeutic Modalities To Interfere With Lp(a)mentioning
confidence: 82%